2019
DOI: 10.1177/1555412019865848
|View full text |Cite
|
Sign up to set email alerts
|

How Does Games Critique Impact Game Design Decisions? A Case Study of Monetization and Loot Boxes

Abstract: Games critics arguably influence the form games take, identities of players, and identities of game developers. However, very little work in Game Studies examines how critical games journalism, games, developers, and independent actors intersect. This article argues that pragmatic sociology of critique, developed by Luc Boltanski, can act as a theoretical framework to aid in understanding these processes of critique. Utilizing a theoretical lens such as this helps us better understand the function of games cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Platforms-the main business structure of contemporary capitalism (Srnicek & De Sutter, 2017)-are the most lucrative assets of today, as, according to Sadowski (2020), their owners capture value by providing multiple actors with access to existing digital resources in exchange for different types of rent. Similarly, the modern video games, with their planned massive content update, and indirect monetization approaches (Nieborg, 2016a), which require smaller but more frequent transactions to access a richer gaming experience (Perks, 2019), can also be seen as (small) platforms. What unites these types of property is that they all capture value through economic rents extracted over time from property users.…”
Section: The Assetization Of the Triple-a Gamementioning
confidence: 99%
See 1 more Smart Citation
“…Platforms-the main business structure of contemporary capitalism (Srnicek & De Sutter, 2017)-are the most lucrative assets of today, as, according to Sadowski (2020), their owners capture value by providing multiple actors with access to existing digital resources in exchange for different types of rent. Similarly, the modern video games, with their planned massive content update, and indirect monetization approaches (Nieborg, 2016a), which require smaller but more frequent transactions to access a richer gaming experience (Perks, 2019), can also be seen as (small) platforms. What unites these types of property is that they all capture value through economic rents extracted over time from property users.…”
Section: The Assetization Of the Triple-a Gamementioning
confidence: 99%
“…As Triple-A publishers turn away from churning out sequels toward continuous support of the existing catalog of games (Hiller, 2017;Tassi, 2019), the classic premium monetization model of singular unitary high-value commodities becomes amalgamated and replaced with alternative approaches (Perks, 2019). Platform capitalism shifts toward assetization or "the transformation of things into resources which generate income without a sale" (Birch, 2015, p. 122).…”
Section: Introductionmentioning
confidence: 99%
“…Turning first to media pressure, from both a theoretical 111 and practical 112 perspective it has been demonstrated that not only are games companies acutely aware of the effect that negative media attention has brought in relation to loot boxes, but they have been willing to act in such a way so as to placate this pressure.…”
Section: The Self-regulatory Approach -mentioning
confidence: 99%
“…Yet, as we discuss, video game developers seem willing to try to extract as much money as they can from consumers through what many people consider increasingly dubious methods. As Perks (in press) noted, the economic decisions of game developers have been facing increased scrutiny.…”
Section: Price Gougingmentioning
confidence: 99%